Influence of Dietary Long-Chain Polyunsaturated Fatty Acids and ω6 to ω3 Ratios on Head Kidney Lipid Composition and Expression of Fatty Acid and Eicosanoid Metabolism Genes in Atlantic Salmon (Salmo salar) - Katan, Tomer; Xue, Xi; Caballero-Solares, Albert; Taylor, Richard G.; Rise, Matthew L.; Parrish, Christopher C. (Frontiers in Molecular Biosciences, 2020)
The interaction of dietary eicosapentaenoic acid and docosahexaenoic acid (EPA+DHA) levels with omega-6 to omega-3 ratios (ω6:ω3), and their impact on head kidney lipid metabolism in farmed fish, are not fully elucidated. We investigated the influence of five plant-based diets (12-week exposure) with varying EPA+DHA levels (0.3, 1.0, or 1.4%) and ω6:ω3 (high ω6, high ω3, or balanced) on tissue lipid composition, and transcript expression of genes involved in fatty acid and eicosanoid metabolism in Atlantic salmon head kidney. Fatty acid composition was reflective of the diet with respect to C18 PUFA and MUFA levels (% of total FA), and ω6:ω3 (0.5-1.5). Fish fed 0.3% EPA+DHA with high ω6 (0.3%EPA+DHA↑ω6) had the highest increase in proportions (1.7-2.3-fold) and in concentrations (1.4-1.8-fold) of arachidonic acid (ARA). EPA showed the greatest decrease in proportion and in concentration (by ~ ½) in the 0.3%EPA+DHA↑ω6 fed fish compared to the other treatments. However, no differences were observed in EPA proportions among salmon fed the high ω3 (0.3 and 1.0% EPA+DHA) and balanced (1.4% EPA+DHA) diets, and DHA proportions were similar among all treatments. Further, the transcript expression of elovl5a was lowest in the 0.3%EPA+DHA↑ω6 fed fish, and correlated positively with 20:3ω3, 20:4ω3 and EPA:ARA in the head kidney. This indicates that high dietary 18:3ω3 promoted the synthesis of ω3 LC-PUFA. Dietary EPA+DHA levels had a positive impact on elovl5a, fadsd5 and srebp1 expression, and these transcripts positively correlated with tissue ΣMUFA. This supported the hypothesis that LC-PUFA synthesis is stimulated by MUFA levels in Atlantic salmon. The expression of pparaa was higher in the 0.3%EPA+DHA↑ω6 compared to the 0.3%EPA+DHA↑ω3 fed fish. Finally, significant correlations between head kidney fatty acid composition and the expression of eicosanoid synthesis-related transcripts (i.e. 5loxa, 5loxb, cox1, cox2, ptges2, ptges3, and pgds) illustrated the constitutive relationships among fatty acids and eicosanoid metabolism in salmon.